Socio-economic inequalities in oral health among Portuguese older adults: a cross-sectional study - Inês Caetano Santos; Giancarlo De la Torre Canales; David G. Lopes; José João Mendes; Mário Polido; Ana Cristina Manso; Helena Canhão (BMC Public Health)
Abstract Background Although the oral health status has improved in developed countries in recent years, oral diseases are still unequally distributed across socio-economic groups. Research on the impact of socio-economic factors on oral health care among older adults in Europe, including Portugal, remains limited. The main aim of this study was to investigate the association between socio-economic factors and oral health indicators in Portuguese older adults. Methods This retrospective cross-sectional study analyzed data from 915 participants (aged 65 years and older) from the third wave (2015–2016) of the Epidemiology of Chronic Diseases Cohort Study (EpiDoC), a population-based study. Socio-economic and demographic information, general health-related characteristics and oral health data (prosthetic need, oral hygiene frequency, and last dental procedure) were collected by questionnaire. Multivariate logistic and multinomial regression models analyzed the associations between socio-economic factors and oral health indicators. Results Participants with lower education level, perceived lower income and a fewer number of private sector appointments were more likely to have poor oral health (need for prosthetic treatment, less frequent oral hygiene, and tooth extraction as last dental procedure). Other factors found to be associated with oral health were sex, age, geographical area, smoking habits, and body mass index. Conclusions Socio-economic factors were associated with oral health in Portuguese older adults. These findings may contribute to future national public health strategies by expanding oral health services to ensure better access and coverage for at-risk groups.